Translating bioenergy policy in Europe: Mutation, aims and boosterism in EU energy governance. Issue 87 (December 2017) - Albrecht, Moritz; Kortelainen, Jarmo; Sawatzky, Matthew; Lukkarinen, Jani; Rytteri, Teijo
Abstract: Supranational policies move from their places of spatial design towards domestic and local materialization, a journey on which policy programs are subject to multiple loops of translation in various spatial contexts. These loops involve shifting rationalities, historically formed path dependencies and distinct constellations of stakeholders, all of which affect the means of their implementation within national and regional socio-spatial environments. This article evaluates the complexity of governance assemblages based on the translation and mutation of European Union bioenergy policies. As part of the transition towards a low carbon economy, EU member states have been given the responsibility to choose their own approaches within the common EU 2020 renewable energy framework. While EU documents highlight energy security, energy union and sustainability, a contested policy translation process reformulates governance means and aims along the way and sometimes causes the generic targets to vanish. Thus, context dependent decision making assemblages are portrayed as shaping the policy process and the advancement of renewable energy in various directions. The article bundles the empirical results of case studies in Finland, Germany, Estonia, France, and Norway, as well as EU institutions in Brussels to conceptualize peculiarities that guide policy design, translation and boosterist processes in transnational governance.